A Description of Scapular Biomechanics in the Windmill Softball Pitch in Early High School Pitchers - Holtz, Kaila A.; Lerch, Benjamin; Zaremski, Jason L.; Butler, Lauren; Ulman, Sophia; Zappa, Ryan; Fava, Anthony; Oliver, Gretchen D. (International Journal of Sports Medicine, 2025)
The scapula facilitates the windmill pitching motion, providing a stable base for the shoulder muscles to accelerate the humerus. Given the repetitive range of motion facilitated by the shoulder musculature about the scapula, shoulder overuse injuries are a significant concern in softball pitchers. Therefore, we aimed to provide normative values of scapular kinematics during the windmill pitching motion in high school-aged softball pitchers. Kinematic data from 17 high school-aged softball pitchers (15±1 y; 1.7±0.1 m; 72.3±15.0 kg) throwing fastball pitches at regulation distance 13.1 m (43 ft) were obtained using an electromagnetic tracking system synced with motion analysis. Scapular kinematics throughout the windmill pitching motion indicated that the scapula maintains an anteriorly tilted and internally rotated (protracted) position while moving within 5 and 22° in each plane, respectively. Additionally, on average, the scapula remained upwardly rotated throughout the start and top of the pitch, through foot contact, but moved into downward rotation at ball release. Description of scapular biomechanics during the windmill softball pitch is an area that has not been extensively researched. Our data reinforce the significance of the scapula as a dynamic stabilizer of the shoulder and its critical role in the kinematics and kinetics of the fastpitch softball windmill pitch.
Keywords: biomechanics; scapula; softball pitching; windmill softball pitch